1981
DOI: 10.1113/jphysiol.1981.sp013838
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and post‐synaptic actions of botulinum toxin at the rat neuromuscular junction.

Abstract: SUMMARY1. Extensor digitorum longus muscles of rats were paralysed with local, non-lethal doses of botulinum toxin Type A (BoTx). At 2 and 7 days after toxin injection, the nerve-muscle preparations were excised and end-plate currents analysed at 23 'C by dual-micro-electrode voltage clamp.2. At 2 days after BoTx injection, the growth time of miniature end-plate currents (m.e.p.c.s) increased from a rather narrow range with a mean of 0-59 to a mean of 1-35 ms with a large variability between m.e.p.c.s. End-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 18 publications
2
27
0
1
Order By: Relevance
“…These m.e.p.p.s have a more variable, but generally much longer, time-to-peak than m.e.p.p.s at unpoisoned junctions, and their amplitude is frequently larger, shifting the distribution of m.e.p.p. amplitudes towards the right (Sellin & Thesleff, 1981;Colmeus, Gomez, Molgo6 & Thesleff, 1982;Thesleff, Molgo & Lundh, 1983). Fundamentally, these m.e.p.p.s differ from those at unpoisoned junctions by being unaffected in frequency by procedures which alter extra-or intracellular Ca2+ concentrations.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…These m.e.p.p.s have a more variable, but generally much longer, time-to-peak than m.e.p.p.s at unpoisoned junctions, and their amplitude is frequently larger, shifting the distribution of m.e.p.p. amplitudes towards the right (Sellin & Thesleff, 1981;Colmeus, Gomez, Molgo6 & Thesleff, 1982;Thesleff, Molgo & Lundh, 1983). Fundamentally, these m.e.p.p.s differ from those at unpoisoned junctions by being unaffected in frequency by procedures which alter extra-or intracellular Ca2+ concentrations.…”
mentioning
confidence: 97%
“…It is concluded that enhancement ofslow m.e.p.p. frequency in muscles poisoned INTRODUCTION Botulinum toxin type A (BoTx) is a presynaptically acting neurotoxin with a specific and long-lasting effect at cholinergic nerve endings (for recent reviews, see Simpson, 1981;Sellin, 1981). At the neuromuscular junction its actions are characterized by a block of impulse-evoked release of acetylcholine (ACh) and by a marked reduction in the frequency of spontaneous miniature end-plate potentials (m.e.p.p.s).…”
mentioning
confidence: 99%
“…The conductance was obtained from y = 12/(l.E) where 12 is the current noise variance, I the mean current passed and E the clamp potential. The reversal potential was taken as o mV (Colquhoun et al, 1977;Sellin & Thesleff, 1981;Alema et al, 1981). Corrections were made throughout to n, a and y for the effects of the low pass filters used (Colquhoun et al, 1977).…”
Section: Electrophysiological Recordingmentioning
confidence: 99%
“…Botulinum toxin (BTX) is a potent neurotoxin synthesized by the Gram-negative, anaerobic, spore-forming bacterium Clostridium botulinum. It blocks presynaptic release of Ach into the end plate of the neural junction, thus leading to reduced activity of muscles or glands (13). Until recently, increasing research has suggested independent actions of BTX on peripheral nociceptors by blocking release of neurotransmitters, including pain and inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%